Конструктивно-продукційне моделювання розподілу енергії рекуперації на основі нечіткої логіки - Іванов, Олександр Петрович; Гуда, Антон Ігорович; Саблін, Олег Ігорович; Шинкаренко, Віктор Іванович (Український державний університет науки і технологій, ННІ ≪Дніпровський металургійний інститут≫, ІВК ≪Системні технології≫, Дніпро, 2025)
UKR: Раніш розроблена конструктивно-продукційна модель ділянки електропостачання тяги постійного струму та її збагачення інформацією значень атрибутики складових елементів. У цій роботі засобами конструктивно-продукційного моделювання та нечіткої логіки на основі експертних даних формується система керування розподілом енергії рекуперації. Розроблена конструктивно-продукційна модель дозволяє формувати текстовий файл у форматі ftl, який є вхідним у системі fuzzyTech. Система fuzzyTech дає можливість засобами нечіткого виводу, враховуючи стан електрообладнання ділянки електропостачання та поїздної ситуації, визначити раціональний розподіл енергії рекуперації керуючи станом перемикачів на підстанціях живлення постійного струму. Цей підхід продемонстровано на прикладі сформованої схеми лінійної ділянка електропостачання з трьома підстанціями та двома потягами.

ENG: This article is the last of three that collectively explore solutions to the problem of regenerative energy distribution for its rational use. The solution is achieved through constructive-production modeling. Previously, a general constructive-production model of a direct current traction power supply section was developed and enriched with information on the attribute values of its constituent elements. In this work, based on expert data, a system for managing the distribution of regenerative energy is formed using constructive-production modeling and fuzzy logic. The developed model allows the formation of a text file in FTL format, which is used in the fuzzyTECH system. FuzzyTECH, in turn, implements fuzzy inference mechanisms, considering the state of electrical equipment and the current situation on the power supply section, to efficiently distribute regenerative energy by controlling switches at direct current power supply substations. This approach is illustrated using a schematic of a linear power supply section with three substations and two trains. The developed models open new opportunities for improving energy efficiency, particularly in railway and urban public electric transport. The primary tasks of the system include identifying the existing traction substation equipment and assessing its technical characteristics, as well as optimizing the use of regenerative energy. Moreover, the proposed approach can be useful for solving issues related to the design of traction power supply systems, enhancing their reliability, and reducing energy losses. Additionally, the implementation of fuzzy logic methods and constructive-production modeling not only improves the management of regenerative energy distribution but also creates a universal approach that can be adapted to other types of electric transport. The proposed system has the potential for integration with intelligent networks and modern energy-saving technologies, opening new perspectives for the development of efficient transportation solutions.
Constructive-Synthesizing Modeling of Recovery Energy Distribution Based on Fuzzy Logic
О. Іванов: ORCID 0000-0003-1259-6377; А. Гуда: ORCID 0000-0003-1139-1580; О. Саблін: ORCID 0000-0001-6784-648X; В. Шинкаренко: ORCID 0000-0001-8738-7225
Keywords: конструктивно-продукційне моделювання; тяга постійного струму; формальні граматики; конструктор; нечітка логіка; програмне забезпечення; інформаційні технології; constructive-synthesizing modeling; direct current traction; formal grammars; constructor; fuzzy logic; software; information technologies; КІТС; КІТ; КЕЦБ; TECHNOLOGY::Information technology